Work Program Implications of KKN Nusantara in Developing Moderate Character Based on Indicators of Religious Moderation - I Dewa Gede Darma Permana Dewa; Dewa Gede Hendra Divayana; I Nyoman Pasek Nugraha (Universitas Pendidikan Ganesha, 2025)
Exclusiveness is a challenge for Indonesia as a pluralistic nation. Based on the data, cases of intolerance have even begun to target the world of education. In response to this challenge, religious universities in Indonesia have come together to implement a collaborative program called Nationhood Community Program Service, which is well-known as Kuliah Kerja Nyata (KKN) Nusantara. However, there has been no description of the form and implications of the program in concrete terminologies. This research aims to examine in depth the essence and implications of KKN Nusantara in developing the moderate character based on the Concept of Religious Moderation. This research utilized a qualitative type, with a phenomenological approach. Through purposive sampling technique, the main data was obtained through interviews with student representatives, lecturers, and the community. The data was then corroborated with a literature study, validated using triangulation techniques, and analyzed using the Miles and Huberman approach. The results showed that the essence of KKN Nusantara is presented as an embodiment of the Tri Dharma of Higher Education and is expressed in the form of several work programs, including Independence Day Celebrations, the introduction to holy places, socialization of religious moderation, and preservation of local culture. As a conclusion, the implementation of KKN Nusantara produces positive implications in developing the moderate character of the community based on the Concept of Religious Moderation, both towards the attitude of national commitment, tolerance, non-violence, and accommodation for local culture.